2022
DOI: 10.3390/nu14142783
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Effects of Traditional and Commercial Kochujang in Overweight and Obese Adults: A Randomized Controlled Trial

Abstract: Kochujang shows anti-obesity effects in cell and animal models. Kochujang is traditionally prepared via slow fermentation or commercially using Aspergillus oryzae. We analyze the anti-obesity effects of two types of Kochujang in overweight and obese adults. The analyses included the following groups: traditional Kochujang containing either a high-dose (HTK; n = 19), or a low-dose of beneficial microbes (LTK; n = 18), and commercial Kochujang (CK; n = 17). Waist circumference decreased significantly in the HTK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…As such, this study was assessed as having some concerns due to missing outcome data and selective reporting. Han et al [70] was found to be of some concern regarding selective non-reporting, as it did not present any between-group analysis data; we were unable to ascertain, despite inquiries, whether analysis was performed, or if no significant differences were found and therefore unreported. In all other studies with dropouts, the authors documented the reasons for missing outcome data, which were all unrelated to the outcomes (e.g.…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 76%
See 4 more Smart Citations
“…As such, this study was assessed as having some concerns due to missing outcome data and selective reporting. Han et al [70] was found to be of some concern regarding selective non-reporting, as it did not present any between-group analysis data; we were unable to ascertain, despite inquiries, whether analysis was performed, or if no significant differences were found and therefore unreported. In all other studies with dropouts, the authors documented the reasons for missing outcome data, which were all unrelated to the outcomes (e.g.…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 76%
“…[53,60,64,65] Akamine et al [62] also reported no dropouts, but only analysed 88% of participants for plasma SCFA, and 85% of participants for faecal microbiota composition, due to missing or uncollected samples. Analysis of over 90% of randomised participants (91 to 96%) was conducted in ten studies; [55,[57][58][59]63,[66][67][68][69][70] all of these studies used per-protocol analysis. Between 80 to 90% of participant data was analysed in five studies, [71][72][73][74][75] with only Cha et al [72] and Oh et al [73] using intention-to-treat analysis for missing data.…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 99%
See 3 more Smart Citations